ChemInform Abstract: Common Metal of Copper(0) as an Efficient Catalyst for Preparation of Nitriles and Imines by Controlling Additives. Issue 35 (2nd September 2014) - Wang, Jiaqing; Lu, Shuanglong; Cao, Xueqin; Gu, Hongwei
Abstract An efficient and environmentally friendly method for copper(0)‐catalyzed oxidation of benzylamines in the presence of 1 equiv.